REACHING THE UNDERSTANDING OF THE GREEN BUILDING CONCEPT IN ISLAMIC VALUE: THEMATIC TAFSEER STUDY - Aulia Fikriarini; Dewi Larasati; Sugeng Triyadi S. (Journal of Islamic Architecture, 2021)
This research is significant to fill the gaps in the development of green building concepts that give an emphasis to the technical strategies or solutions. This study used the thematic Quranic interpretation method (maudhu'i). It was done by collecting verses from the Quran related to the environment in general, specifically using quantitative content analysis. The result shows that there are two significant main categories stated for greenship based on thematic, mainly ASD and WAC. It reaches the most vital points. It is 56.1% points of ASD and 28.5% of WAC. It is expected that, by applying this approach, the green building concept will be much easier to be accepted, understood by human being as caliphs, and implemented as well as possible.